Сезонные биоритмы функциональной системы "мать-плацента-плод" в зависимости от её стереофункциональной организации при физиологической и осложнённой беременности - Боташева, Т.Л.; Рогова, Н.А.; Черноситов, А.В.; Каушанская, Л.В.; Шубитидзе, М.Г. (Таврический медико-биологический вестник, 2013)
У роботі представлено результати аналізу періодограм зачать, контрактильної активності правих і лівих відділів матки, акушерської патології та ваго-ростових показників новонароджених у різні сезони року. Виявлено, що частота народження загрози передчасних пологів, а також характерного для них двостороннього патерну маткової активності, мала період 7 місяців. Збільшення числа великих дітей відзначалося восени і взимку, в літній період частіше народжувалися діти з низькою масою тіла. Найбільша маса новонароджених відзначалася при амбілатеральному розташуванні плаценти, найменша – при лівосторонньому. The article presents the results of the analysis of conception periodograms, contractive activity of the right and left parts of the uterus, obstetric pathology, newborns’ weight and growth parameters in different seasons. We have established that the incidence of preterm birth, as well as that of the bilateral uterine activity pattern typical for it, has a period of 7 months. We also observed an increase in the number of largeweight children in autumn and winter, more babies with low birth weight were born in summer. We observed a maximum weight of infants at ambilateral localization of placenta; a minimum weight of infants was observed in left-oriented placentation.